The France of the little-middles : a suburban housing development in greater Paris - Cartier, Marie; Coutant, Isabelle; Masclet, Olivier; Siblot, Yasmine (Anthropology of Europe (Series), 2019)
The Poplars housing development in suburban Paris is home to what one resident called the 'Little-Middles' ' a social group on the tenuous border between the working- and middle- classes. In the 1960s The Poplars was a site of upward social mobility, which fostered an egalitarian sense of community among residents. This feeling of collective flourishing was challenged when some residents moved away, selling their homes to a new generation of upwardly mobile neighbors from predominantly immigrant backgrounds. This volume explores the strained reception of these migrants, arguing that this is less a product of racism and xenophobia than of anxiety about social class and the loss of a sense of community that reigned before.